Comparison of gingival crevicular fluid levels of IL-1b and IL-6 in subjects with gingivitis and stage III grade C periodontitis - Dikilitaş Ahu; Karaaslan Fatih; Seçkin Ertuğrul Abdullah (Balkan Journal of Dental Medicine, 2022)
Background/Aim: Periodontal diseases are inflammatory diseases that occur against microbial pathogens. Cytokines are biologically active molecules involved in this inflammatory process. This study aims to evaluate interleukin-1 beta (IL-1b) and interleukin-6 (IL-6) cytokine levels in the gingival crevicular fluid (GCF) of individuals with stage III grade C (SIIIGC) periodontitis, gingivitis (G) and periodontally healthy (PH). Material and Methods: A total of 64 individuals, including 22 PH, 22 G and 20 SIIIGC periodontitis were included in this study. Plaque index (PI), gingival index (GI), bleeding on probing (BOP), probing pocket depth (PPD), and clinical attachment loss (CAL) parameters were evaluated. GCF samples were analyzed by enzyme-linked immunosorbent assay (ELISA) kits. Results: IL-1b and IL-6 levels in the GCF were significantly higher in the SIII-GC periodontitis group compared to the other groups (P <0.05). There was no significant difference between IL-1b and IL-6 levels in the PH and G groups (P > 0.05). GCF IL-1b and IL-6 levels were positively associated with the whole mouth and sampling area clinical periodontal parameters (P < 0.001). Conclusions: GCF IL-1b and IL-6 total amounts are effective in determining the regions and individuals under risk in SIII-GC periodontitis. Moreover, GCF IL-1b and IL-6 levels were seen to be effective determinants in differentiating gingivitis and periodontitis.